Tracking Pesticide Residues to a Plant Genus Using Palynology in Pollen Trapped from Honey Bees (Hymenoptera: Apidae) at Ornamental Plant Nurseries - Stoner, Kimberly A (Environ Entomol, 2019)
Worldwide studies have used the technique of pollen trapping, collecting pollen loads from returning honey bee (Apis mellifera L.) (Hymenoptera: Apidae) foragers, to evaluate the exposure of honey bees to pesticides through pollen and as a biomonitoring tool. Typically, these surveys have found frequent contamination of pollen with multiple pesticides, with most of the estimated risk of acute oral toxicity to honey bees coming from insecticides. In our survey of pesticides in trapped pollen from three commercial ornamental plant nurseries in Connecticut, we found most samples within the range of acute toxicity in a previous state pollen survey, but a few samples at one nursery with unusually high acute oral toxicity. Using visual sorting by color of the pollen pellets collected in two samples from this nursery, followed by pesticide analysis of the sorted pollen and palynology to identify the plant sources of the pollen with the greatest acute toxicity of pesticide residues, we were able to associate pollen from the plant genus Spiraea L. (Rosales: Rosaceae) with extraordinarily high concentrations of thiamethoxam and clothianidin, and also with high concentrations of acephate and its metabolite methamidophos. This study is the first to trace highly toxic pollen collected by honey bees to a single plant genus. This method of tracking high toxicity pollen samples back to potential source plants could identify additional high-risk combinations of pesticide application methods and timing, movement into pollen, and attractiveness to bees that would be difficult to identify through modeling each of the contributing factors.